2021
DOI: 10.3390/jcdd8100133
|View full text |Cite
|
Sign up to set email alerts
|

Combined Use of Electrocardiography and Ultrasound to Detect Cardiac and Pulmonary Involvement after Recovery from COVID-19 Pneumonia: A Case Series

Abstract: Background: Although severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) may cause an acute multiorgan syndrome (coronavirus disease 2019 (COVID-19)), data are emerging on mid- and long-term sequelae of COVID-19 pneumonia. Since no study has hitherto investigated the role of both cardiac and pulmonary ultrasound techniques in detecting such sequelae, this study aimed at evaluating these simple diagnostic tools to appraise the cardiopulmonary involvement after COVID-19 pneumonia. Methods: Twenty-nine p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 39 publications
(69 reference statements)
0
3
0
Order By: Relevance
“…Our case series suggests that the majority of vulnerable patients may exhibit cardiopulmonary complications during the acute phase of SARS-CoV-2 infection contracted during hospitalization. Of note, these cardiac complications appear to be comparable to those noted in the early phase of the pandemic [ 8 , 9 , 11 15 ]. A non-negligible proportion of patients may react with a significant increase in BP.…”
Section: Discussionmentioning
confidence: 60%
“…Our case series suggests that the majority of vulnerable patients may exhibit cardiopulmonary complications during the acute phase of SARS-CoV-2 infection contracted during hospitalization. Of note, these cardiac complications appear to be comparable to those noted in the early phase of the pandemic [ 8 , 9 , 11 15 ]. A non-negligible proportion of patients may react with a significant increase in BP.…”
Section: Discussionmentioning
confidence: 60%
“…In a recent study, Marrazota et al . concluded that a simple combination of transthoracic echocardiography and LUS can unravel many cardiopulmonary complications that potentially follow COVID-19 pneumonia [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…The combination of LUS and echocardiography has had a great impact on treatment decisions [54,59]. There are many case reports that report cardiac involvement in COVID-19-affected patients [60].…”
Section: Cardiovascular and Hemodynamic Assessmentmentioning
confidence: 99%